Answer :

Given:


(1-3x+10x2)n


Sum of coefficients = a


a


=(23)n


=(2n)3


(1+x2)n


Sum of coefficients = b


b= (1+1)n


=2n


Put value of b in a; we get:


a=b3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that RS Aggarwal - Mathematics

Using binominal tRS Aggarwal - Mathematics

Evaluate :
</p
RS Aggarwal - Mathematics

Using binomial thRS Aggarwal - Mathematics